Academic and employment status of Costa Rican female university graduates during the 2011-2016 period - Azofeifa Ureña, Cinthia; Corrales Bolívar, Karen; Sandí Araya, Katherine (Actualidades Investigativas en Educación, 2023)
This study aims to investigate the labor and academic status of female university graduates in Costa Rica between 2011 and 2016, utilizing statistical analyses and designated zones for assessment to identify gender gaps in employment and academia. The research adopts a quantitative approach, incorporating descriptive statistics, the development of labor related indicators, and statistical ratios. Data from the Labor Condition Monitoring Studies of Costa Rican university graduates for the periods 2011-2013 and 2014-2016, collected in 2016 and 2019, respectively, were utilized. The sample included 14,435 graduates from both public and private universities. Results indicate that women faced significant unemployment gaps across all four analysis zones (stone, evolution, risk, and 4.0). In terms of the employment to career relationship indicator, two of the four zones exhibited unfavorable outcomes for women. Additionally, the indicator of underemployment due to insufficient hours showed negative trends for women. Despite their qualifications in science, technology, mathematics, and engineering fields, women encountered difficulties in attaining similar employment conditions as their male counterparts, leading to the persistence of gender gaps in all analysis zones, with the Evolution and 4.0 zones showing more pronounced disparities.